Geomorphological control of quartzites in the Borborema Province: The case of the reliefs of Ceará, Brazil - Diógenes, Davi Henrick Veras; Bastos, Frederico de Holanda; dos Santos, Luzia Suerlange Araújo (Revista Brasileira de Geomorfologia, 2026)
The state of Ceará presents a complex morphostructural context due to the diversity of lithotypes and the structural framework that make up its territory. In a geomorphological evolution context of a transform margin under a semi-arid climate, the differential resistance of rocks to weathering plays a fundamental role in shaping the relief. Within this scenario, the present study aims to analyze quartzites from different geological units outcropping in Ceará, seeking to assess their physical and mechanical properties through laboratory tests, and to discuss how these characteristics influence the preservation of landforms. A total of 24 quartzite samples, belonging to 13 distinct geological units, were analyzed, providing data on uniaxial compressive strength, physical indices, abrasion resistance, wave propagation velocity, and petrographic characteristics, in addition to analyses of the state’s geomorphological context using a DEM. Understanding aspects such as low solubility, mechanical strength, degree of microfracturing, structure, and mineralogical composition of the different quartzites was essential for interpreting their important role in the preservation of ridges and massifs throughout the state territory as a result of differential erosion.